Factors Affecting Understandibility of Micro, Small, and Medium Enterprises in Preparation of Financial Statement Based on SAK ETAP in Palembang - Anton Indra Budiman; Rina Tjandrakirana; Rochmawati Daud; Ermadiani Ermadiani; Harun Delamat; Burhanuddin Burhanuddin; Ubaidillah Ubaidillah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
The role of MSMEs (Micro, Small and Medium Enterprises) are to improve the economy and reduce the unemployment in Indonesia is widely significant regarding to the growth of MSME growth in every year. However, MSMEs often find some problem which obstruct its business growth especially about the ffunding. The phenomena that exist today, many MSMEs only using funds/private capital to develop their business with reason their business is still in early growth. In fact, instead in early growth, MSMEs must do the innovation in order to be more competitive in the marketplace. In 2015, Indonesia was starting to face Asean Economic Community (AEC) where as the market competition will be more competitive for MSMEs. Therefore, to provide private capital also required other capital (loans) from third parties to fund the business growth of MSMEs. The reason why  MSMEs do not make loans from other parties is about the unavailability of the financial statements based on SAK ETAP which can facilitate to access bank lending. Unavailability of financial statements in accordance with SAK ETAP on MSMEs has several factors, namely, costs are relatively expensive to pay for experts in the field of accounting, a lack of understanding in presenting financial statement based on SAK ETAP and the perceptions of MSMEs that considesr the financial statements are not urgency to do. This research aims to obtain empirical evidences whether the giving of information and socialization, educational background, level of education, size of enterprises and long effect on the understanding of MSMes in presenting financial statements based on SAK ETAP on MSMEs. The object in this study is MSMEs in Palembang city with number of respondents of 40 MSMEs with characteristics of small and medium enterprises. Data retrieval in this study using a questionnaire which is then processed using logistic regression analysis. The results of the study prove that giving information and socialization, educational background, level of education and business size do not affect on the understanding of MSMes in presenting financial statements based on the SAK ETAP on MSMEs. Only long effect affect on the understandability of MESMEs in presenting the financial statement.